2013
DOI: 10.1007/s10103-013-1351-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of power density of light-curing units used in private dental offices in Changchun City, China

Abstract: This study investigated power density and relevant information related to light-curing units used in private dental offices in Changchun City, China. The power density of 196 light-curing units used in private dental offices in Changchun City was measured using a simple random sampling method. Relevant information included the brand, type, years of operation, frequency of use, model numbers and types of light guide, resin buildup on the light guides, damage caused by the light guides, required maintenance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
1
18
0
6
Order By: Relevance
“…In opposition, Hao, et al 15 (2013) observed that the majority of light-curing units used by Chinese dentists were QTH units, with several years of use. Also, the authors observed that dentists were not aware of the need of periodic testing and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In opposition, Hao, et al 15 (2013) observed that the majority of light-curing units used by Chinese dentists were QTH units, with several years of use. Also, the authors observed that dentists were not aware of the need of periodic testing and maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that the variation of some physical parameters can significantly change the resin shrinkage during the curing process, concluding that the radiant exitance (or emittance) of the curing device has a correlation with the volumetric contraction induction of photopolymerized composite resins 9 , 15 , 18 . It has been observed a variation of shrinkage stress when the composite is polymerized under different conditions of exposure to the luminous source, being that some studies showed that the irradiance modulation during the photoactivation process has an influence on the shrinkage stress modulus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 To date, every study published that has evaluated light curing units (LCU) used in dental offices has shown that many are delivering an inadequate light output and are also poorly maintained. 40,41,42,43,44,45,46,47 In addition to being an averaged value that has been calculated from the power output divided by the tip area, the irradiance values stated by the manufacturers are usually measured only at the light tip. These values can give the dentist the impression they are using a "powerful" curing light, but significantly lower irradiance may be reaching the surface of the resin that is often at least 2 to 8 mm away from the light tip.…”
Section: Effect Of Light Tip To Resin Distancementioning
confidence: 99%